2006
DOI: 10.1534/genetics.105.054486
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding by Environmental Interactions Affect Gene Expression in Drosophila melanogaster

Abstract: Genomewide gene expression patterns were investigated in inbred and noninbred Drosophila melanogaster lines under benign and stressful (high temperature) environmental conditions in a highly replicated experiment using Affymetrix gene chips. We found that both heat-shock protein and metabolism genes are strongly affected by temperature stress and that genes involved in metabolism are differentially expressed in inbred compared with noninbred lines, and that this effect is accentuated after heat stress exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 33 publications
8
106
4
Order By: Relevance
“…The relationship between stress and within-line, or microenvironmental, variance is not as clear, in part because studies tend to report within-line variance but do not test hypotheses about it (for example, Fry and Heinsohn, 2002). Several studies have documented increases in microenvironmental variance with exposure to a new, and generally stressful, environment (for example, Rutter et al, 2010); this increased variance could reflect variance in expression of individual genes (for example, Kristensen et al, 2006). As expected, given previous work with Caenorhabditis MA lines (Baer, 2008;Matsuba et al, 2012), we detected higher within-line variance in the low-fitness MA lines than in the high-fitness MA lines.…”
Section: Discussionsupporting
confidence: 81%
“…The relationship between stress and within-line, or microenvironmental, variance is not as clear, in part because studies tend to report within-line variance but do not test hypotheses about it (for example, Fry and Heinsohn, 2002). Several studies have documented increases in microenvironmental variance with exposure to a new, and generally stressful, environment (for example, Rutter et al, 2010); this increased variance could reflect variance in expression of individual genes (for example, Kristensen et al, 2006). As expected, given previous work with Caenorhabditis MA lines (Baer, 2008;Matsuba et al, 2012), we detected higher within-line variance in the low-fitness MA lines than in the high-fitness MA lines.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies showed that several pathways may be upregulated in inbred as compared with outbred Drosophila individuals, whereas others, though less commonly occurring, are downregulated (Kristensen et al, , 2006Pedersen et al, 2005;García et al, 2012). Similarly, Ayroles et al (2009) showed that inbreeding depression results in an overexpression of many genes associated with metabolism, stress or defence mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, this suggests that dysfunction of mitochondrial function is a major factor in the high mortality observed in the L-line. Other analyses on the molecular consequences of environmental stress, inbreeding and aging have also observed genes related to energy metabolism to be affected (Landis et al, 2004;Kristensen et al, 2006;S rensen et al, 2007). This indicates that energy metabolism is a highly sensitive and fine-tuned process that can respond to a diverse range of stimuli.…”
Section: Mitochondrial-related Processesmentioning
confidence: 93%